Resposta :
Explicação passo-a-passo:
Determine o valor da expressão
82-[8²×7:(4+1×3)]=
82-[64.7:(4+3)]=
82-[64.7:(7)]=
82-[64.1]=
82-[64]=
18
Espero ter ajudado ♥️.
Resposta:
[tex]\sf{segue \: abaixo \: a \: resposta}[/tex]
Explicação passo-a-passo:
[tex]\sf{82-[8²×7:(4+1×3)].}[/tex]
[tex]\sf{82 - ( {8}^{2}x7 \div (4 - 3)) }[/tex]
[tex]\sf{4 + 3 = 7}[/tex]
[tex]\sf{82 - ( {8}^{2} x7 \div 7)}[/tex]
[tex]\sf{82 - ( {8}^{2} x1)}[/tex]
[tex]\sf{82 - {8}^{2} }[/tex]
[tex]\sf{ {8}^{2} } = 64[/tex]
[tex]\sf{82 - 64}[/tex]
[tex]\boxed{\boxed{{\sf{18}}}}[/tex]